2009
DOI: 10.1002/ana.21795
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the subthalamic nucleus and impulsivity: Release your horses

Abstract: Objective-In Parkinson disease (PD) patients, deep brain stimulation (DBS) of the subthalamic nucleus (STN) may contribute to certain impulsive behavior during high-conflict decisions. A neurocomputational model of the basal ganglia has recently been proposed that suggests this behavioral aspect may be related to the role played by the STN in relaying a "hold your horses" signal intended to allow more time to settle on the best option. The aim of the present study was 2-fold: 1) to extend these observations by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
193
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(217 citation statements)
references
References 53 publications
19
193
1
4
Order By: Relevance
“…The possibility of induction of new onset ICD by STN-DBS has been already reported [22], even if other studies demonstrated an improvement of pre-existing ICD after DBS [23]. The central position of the STN within the basal ganglia thalamo-cortical associative and limbic circuits could explain its role in promoting the onset of ICD in some patients [24]; STN-DBS can indeed interfere with the response inhibition pattern, leading to an increase of impulsivity [25]. This finding further supports the necessity of a psychiatric surveillance of the patients after STN-DBS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The possibility of induction of new onset ICD by STN-DBS has been already reported [22], even if other studies demonstrated an improvement of pre-existing ICD after DBS [23]. The central position of the STN within the basal ganglia thalamo-cortical associative and limbic circuits could explain its role in promoting the onset of ICD in some patients [24]; STN-DBS can indeed interfere with the response inhibition pattern, leading to an increase of impulsivity [25]. This finding further supports the necessity of a psychiatric surveillance of the patients after STN-DBS.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to total score (items 18-31), specific subscores were taken into account: bradykinesia (items 19,[23][24][25][26]31), tremor (items 20-21), rigidity (item 22), speech (item 18), gait (item 29), postural stability (item 30) and axial score (items 18, 27-30).…”
Section: Motor Assessmentmentioning
confidence: 99%
“…Otros autores, por el contrario, han referido la aparición de ICD en pacientes tratados con DBS a pesar de la reducción de agonistas DA 49,72,104 . Por último en otros estudios realizados, la estimulación del núcleo subtalámico en pacientes jóvenes, aumentaría el riesgo de desarrollar ICD y en este contexto, no únicamente existiría un incremento en presentar un cuadro de impulsividad, sino también un mayor riesgo de suicidio 12,55,98,103,104,119 .…”
Section: Cirugía De La Ep Aspectos Motores Y No Motoresunclassified
“…Early studies on patients with idiopathic Parkinson's disease (iPD) have demonstrated that the subthalamic nucleus (STN) influences learning and attentional processes, which can either be improved or impaired depending on the task (Jahanshahi et al 2000). More recently, the STN was suggested as relay in the decision making process by providing an inhibitory signal to prevent premature execution of responses in conflicting decisions (Mink 1996;Aron and Poldrack 2006;Frank et al 2007;Thobois et al 2007;Ballanger et al 2009 (Frank 2006) are critical in the early phase of skill acquisition. In particular, STN activity was predicted in Frank's model to increase during trial repetitions '25-60' during early decision making repetitions (Frank 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, STN activity was predicted in Frank's model to increase during trial repetitions '25-60' during early decision making repetitions (Frank 2006). However, the experimental paradigms used in healthy subjects and iPD patients with subthalamic nucleus deep brain stimulation (STN-DBS) were independent of the learning process and included a well-trained probabilistic selection task (Frank et al 2007), a random number generation task (Thobois et al 2007) and a Go/NoGo task (Aron and Poldrack 2006;Ballanger et al 2009). …”
Section: Introductionmentioning
confidence: 99%